Lars Erik Blomqvist (1942 07 03 ‒ 2021 10 10) - Sausverde, Erika (Slavistica Vilnensis, 2021)
Lars Erik Blomqvist was an outstanding Swedish Slavist and celebrated translator of Russian literature. He was awarded numerous prizes for his work as a translator, honored as the best lecturer at Uppsala University, bestowed the degree of doctor honoris causa by Stockholm University, and was one of the founders of the celebrated seminar at Södertörn University focused on the translation of prose and poetry. He translated the works of Bulgakov, Erenburg, Leonov, Aitmatov, Pristavkin, Pjecuch, Pilnyak, Grossman, Bitov, and many others, including the works of Russian classics — Radischev, Tolstoy, Dostoevsky, Sologub. One of the highlights of his translations is the anthology of Russian poetry Från Derzjavin till Brodsky (1989), which was a joint project with Hans Björkegren. Lars Erik visited Vilnius University numerous times, where he gave lectures and master classes on the translation of fiction.